2015
DOI: 10.3389/fpsyt.2015.00165
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones Regulate Cytoskeletal Proteins Involved in Brain Plasticity

Abstract: In the brain of female mammals, including humans, a number of physiological and behavioral changes occur as a result of sex hormone exposure. Estradiol and progesterone regulate several brain functions, including learning and memory. Sex hormones contribute to shape the central nervous system by modulating the formation and turnover of the interconnections between neurons as well as controlling the function of glial cells. The dynamics of neuron and glial cells morphology depends on the cytoskeleton and its as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 187 publications
(195 reference statements)
1
35
0
2
Order By: Relevance
“…Progesterone and estradiol increase steadily across the three trimesters and then return rapidly to baseline following parturition. We know from nonhuman animal studies that hormonal events during gestation and parturition remodel neural circuits such that maternal behavior is induced (Numan, 2012 Arroyo, 2015). Progesterone, for instance, is known to enhance the number of oligodendrocytes (the myelinating glial cells of the central nervous system), the formation of myelin sheath, and synthesis of myelin proteins, directly affecting the process of white matter myelination (Baulieu & Schumacher, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progesterone and estradiol increase steadily across the three trimesters and then return rapidly to baseline following parturition. We know from nonhuman animal studies that hormonal events during gestation and parturition remodel neural circuits such that maternal behavior is induced (Numan, 2012 Arroyo, 2015). Progesterone, for instance, is known to enhance the number of oligodendrocytes (the myelinating glial cells of the central nervous system), the formation of myelin sheath, and synthesis of myelin proteins, directly affecting the process of white matter myelination (Baulieu & Schumacher, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Human pregnancy is characterized by unparalleled increases in sex steroid hormone levels (progesterone and estradiol) that exceed the exposure levels of a woman's entire nonpregnant life(Soma-Pillay et al, 2016). ex vivo and in vitro experiments have shown that sex steroid hormones regulate different aspects of neural plasticity such as changes in dendrite morphology, synaptic connectivity, and glia cells(Garcia-Segura & Melcangi, 2006;Hansberg-Pastor, González-Arenas, Piña-Medina, & Camacho-Arroyo, 2015). We know from nonhuman animal studies that hormonal events during gestation and parturition remodel neural circuits such that maternal behavior is induced(Numan, 2012).…”
mentioning
confidence: 99%
“…Proximal dendritic spines are at a strategical site to modulate the cell body and axonal voltage and the output activity of the MePD. The structure-function coupling of spines and the activity-driven changes related to synaptic demand, stability and plasticity can be set at the level of each single spine (Arellano et al, 2007;Becker, Dall′Oglio, Rigatto, Giovenardi, & Rasia-Filho, 2015;Chen, Leischner, Rochefort, Nelken, & Konnerth, 2011;Dall'Oglio et al, 2015;Dalpian, Brusco, Calcagnotto, Moreira, & Rasia-Filho, 2015;Hansberg-Pastor, González-Arenas, Piña-Medina, & Camacho-Arroyo, 2015;Rochefort & Konnerth, 2012;Stewart et al, 2014). Interestingly, prepubertal males have more stubby/wide spines than prepubertal females.…”
Section: F I G U R Ementioning
confidence: 99%
“…In the last few years, it has been demonstrated that the sex steroid hormones 17-β-estradiol (E2) and progesterone (P4) act as neuromodulators and control multiple vital functions, among them learning and memory [3]. Both hormones can activate signaling pathways that ultimately regulate DS formation, contributing to synaptic plasticity [4][5][6][7]. The lack of E2 and P4 could therefore be harmful for brain functions.…”
Section: Introductionmentioning
confidence: 99%